Relevansi Pendidikan Jasmani dengan Tujuan Pendidikan Islam dalam Membentuk Individu yang Seimbang Secara Fisik, Mental, dan Spiritual - Ari Tri Fitrianto (Sekolah Tinggi Agama Islam Al-Jami Banjarmasin, 2023)
Physical Education and Islamic Education have significant relevance in shaping individuals who are balanced physically, mentally, and spiritually. Physical Education provides a foundation for physical development through physical activities, sports, and games, while Islamic Education emphasizes the formation of character, morality, and spirituality in individuals. The integration of both creates a holistic approach that supports the formation of individuals who are healthy both physically and spiritually. This article discusses how the application of Islamic Education principles in the Physical Education curriculum can enhance the understanding and implementation of Islamic values, such as justice, cooperation, and life balance. By combining these aspects, education becomes a means to shape individuals who not only excel physically but also possess high morality in line with Islamic teachings. Thus, this article proposes a closer integration between Physical Education and Islamic Education as a step towards the comprehensive formation of individuals, both physically and spiritually. Keywords: Relevance, Physical Education, Objectives, Islamic Education